THE REFORM ERA OF POLICING: HOW DOES ORGANIZATIONAL STRUCTURE INFLUENCE ORGANIZATIONAL CULTURE? - Kubra Gultekin (European Scientific Journal, ESJ, 2014)
Police organizational culture is very strong force in shaping individual police officers’ occupational characteristics. Working as a police officer or as a police administrator modifies individuals. While individual officers try to enforce the law and restrict or control the actions of the public to maintain public order, they intentionally or unintentionally change their personal nature. They identify themselves first as police officers and secondly as individuals. How is such a strong occupational culture formed? Does organizational structure influence organizational culture? This study argues that police culture largely shaped in the reform era of policing due to the structural reforms. Structural components affect perceptions of members of organizations, as well as common beliefs. It has been shown that the police generated their own worldview, which is filled with postulates, cultural themes, and ethos in reform era. The concept of professionalization made police organization a bureaucratic organization. Police organizations are granted the use of force and violence in the name of state by the law because they are expected to prevent crime. Police officers are isolated and alienated from the public, who influences police suspicion by exaggerating actual danger of the occupation. Police solidarity is enforced from perceived threat and negative responses by citizens. police organization tried to be autonomous from the rest of the society and developed a we-versus-them attitude among police officers. Accordingly, it can be argued that organizational structure has impact on organizational culture.